2019
DOI: 10.1371/journal.pone.0221064
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping for agronomic traits in six-rowed spring barley from the USA harvested in Kazakhstan

Abstract: In barley, six-rowed barley is advantageous over two-rowed barley for feed due to the larger number of seeds per spike and the higher seed protein content. The growth of six-rowed barley is potentially important for breeding in agriculturally oriented countries, such as Kazakhstan. Nevertheless, until recently, very little attention was given to six-rowed barley in breeding projects in Kazakhstan, one of the largest countries in the world. In this study, phenotyping and single nucleotide polymorphism (SNP) gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
15
0
1
Order By: Relevance
“…Although GWAS has proven to be very effective for capturing relevant marker-trait associations (MTAs) for yield components, results reported from studies in different regions of the world are revealing the tendency for a strong influence of the environmental conditions with significant genotype x environment interaction (GEI) revealed. For example, GWAS results obtained from multilocation studies related to the identification of QTLs for yield performance showed different responses, and QTLs for yield components were identified in different parts of the genome [16,17], similarly to what reported in common wheat [24,8] and barley [25,26,27]. Therefore, the success of regional projects largely relies on local GWA studies based on the evaluation of genetically diverse wild and domesticated germplasm.…”
Section: Introductionmentioning
confidence: 78%
“…Although GWAS has proven to be very effective for capturing relevant marker-trait associations (MTAs) for yield components, results reported from studies in different regions of the world are revealing the tendency for a strong influence of the environmental conditions with significant genotype x environment interaction (GEI) revealed. For example, GWAS results obtained from multilocation studies related to the identification of QTLs for yield performance showed different responses, and QTLs for yield components were identified in different parts of the genome [16,17], similarly to what reported in common wheat [24,8] and barley [25,26,27]. Therefore, the success of regional projects largely relies on local GWA studies based on the evaluation of genetically diverse wild and domesticated germplasm.…”
Section: Introductionmentioning
confidence: 78%
“…The SNP data for this set were acquired from the James Hutton Institute at the Germinate Barley SNP Platforms (629 accessions; https://ics.hutton.ac.uk, accessed date 16 March 2021), from Dr. T. Blake (538 accessions; Montana State University, MT, USA), from National Bioresource Project, Barley, Japan (94 accessions), and from the National Small Grains Collection (NSGC) at the USA National Plant Germplasm System (40 accessions). Except for the samples from the James Hutton Institute, most of the accessions were previously grown in Kazakhstan and analyzed using a genome-wide association study (GWAS) [3,4]. A total of 597 samples of two-rowed barley from North America (279 samples), Europe (123 samples), Western Asia (58 samples), Africa (31 samples), East Asia (9 samples), and South America (3 samples) were used.…”
Section: Barley Snp Genotyping Sourcesmentioning
confidence: 99%
“…In earlier studies, bi-parental mapping populations were used to reliably detect QTL for HD, PH, and spike morphological traits (Lin et al, 1998 ; Sameri et al, 2006 ; Zhang et al, 2009 ). With the emergence of more cost-effective, high-throughput genotyping technologies, single nucleotide polymorphisms (SNPs) related to HD have been identified by genome-wide association studies (GWAS) (Pasam et al, 2012 ; Visioni et al, 2013 ; Genievskaya et al, 2018 ), PH (Alqudah et al, 2016 ; Almerekova et al, 2019 ), leaf area (Alqudah et al, 2018 ), spike architecture (Comadran et al, 2011 ) and grain yield (Ingvordsen et al, 2015 ; Xu et al, 2018 ) in barley. However, the genetic study of complex agronomic traits in qingke barley is limited (Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%